Analiza wpływu lokalizacji stacji metra warszawskiego na ceny mieszkań na przykładzie dzielnicy Ursynów w Warszawie - Marcin Torzewski (Studia i Materiały)
The Warsaw metro plays a key role in the public transport system of the capital: on the one hand, it significantly reduces travel time from peripheries of city to the centre, and on the other hand it makes it easier to commute inside the city. Therefore one could expect that the positive aspects of metro existence should be capitalized by the nearby property values. The purpose of this article is to present the results of an empirical analysis on the impact of the Warsaw metro stations (I line) location on property prices, based on the primary residential market of Ursynów district (Warsaw). The main hypothesis assumes that the distance of a property from the subway station negatively affects a property price. To examine this relationship a hedonic pricing model is applied. Moreover, instead of the traditional approach to measure the distance with the Euclidean metric, the distance between the metro station and the property is measured with the use of GPS module. The results confirm the research hypothesis, showing that an increase of 1 km in the distance between the metro station and the real estate leads to the decline in the property price by approximately 172 PLN/m2 or 2.35%.